Cirillo di Alessandria, Ipazia, l’impero: razionalità e strategie di potere nella violenza tardoantica - Gobbi, Irene (Vox Patrum, 2025)
The first three years of Cyril of Alexandria’s episcopate (412‐415) have returned to ignite the interest of the academic world especially in the last two decades, partly due to the extraordinary relevance that the figure of the Neoplatonic philosopher Hypatia has assumed in the Western cultural imaginary. My investigation aims to inscribe this theory in a much broader framework: in the light of the rare but valuable chronicles covering the first half of the 5th century (Socrates Scholasticus, Damascius, John Malalas, John of Nikiû), the strategies implemented by the bishop and the regent Pulcheria of Constantinople will be compared, thus tracing the events in Alexandria back in greater detail to an organic political line whose roots can be found in a convergence of intentions between the Empire and the most important eastern ecclesiastical See, which later became obvious during the Council of Ephesus.The first three years of Cyril of Alexandria’s episcopate (412‐415) have returned to ignite the interest of the academic world especially in the last two decades, partly due to the extraordinary relevance that the figure of the Neoplatonic philosopher Hypatia has assumed in the Western cultural imaginary. My investigation aims to inscribe this theory in a much broader framework: in the light of the rare but valuable chronicles covering the first half of the 5th century (Socrates Scholasticus, Damascius, John Malalas, John of Nikiû), the strategies implemented by the bishop and the regent Pulcheria of Constantinople will be compared, thus tracing the events in Alexandria back in greater detail to an organic political line whose roots can be found in a convergence of intentions between the Empire and the most important eastern ecclesiastical See, which later became obvious during the Council of Ephesus.